Use linear programming to solve the transportation problem and test optimization solution by modified method - Basher Faisal Mohammed (Journal of Madenat Alelem University College, 2015)
The research solving transportation problem using the entrance of operations research in the analysis phase and the design ofthe problem model, were compared to the results obtained from solutions to the formulation of the analysis and demonstrate the vector model towards the subject’s health, was a comparison between different solutions to choose lower value for the objective function so that the beneficiary of the decision-making , using four methods (the northwest corner method, minimum cost method , Vogel approximate method, Minimum- Cost Sum- Modified Method ),For best results have come to search the modified method by the researcher gave the best steps to solve optimization, it was optimization solution tested using the modified method of distribution (Modi), which gave the best results by reducing the total cost.